2019
DOI: 10.3390/atmos10100574
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Rainfall Events in Southern China Associated with Tropical Cyclones in the Bay of Bengal: A Case Study

Abstract: We use a case study to show that a continuous heavy rainfall process in southern China was closely related to tropical cyclone activity in the Bay of Bengal. The continuous heavy rainfall that occurred in southern China on 11–13 May 2002 can be considered as two different processes. The first process, referred to as a predecessor rain event, occurred over southwestern China before landfall of the tropical cyclone. The second process occurred after dissipation of the tropical cyclone when its remnant caused hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The rainfall over southeastern China was mainly attributed to the baroclinic frontogenesis caused by strong warm, wet advection. Numerous previous studies also revealed that the local conditions favored for heavy rainfall occurrence over southwestern China and southeastern China were different, including the underlying surface conditions, the impact of weather systems and cold air activity (Yuan et al, 2018;Li and Li, 2019;Yuan et al, 2019;Chen and Li, 2022;Li et al, 2022), etc. These findings suggested that the characteristics of rainfall and its mechanisms may have regional differences in southern China.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The rainfall over southeastern China was mainly attributed to the baroclinic frontogenesis caused by strong warm, wet advection. Numerous previous studies also revealed that the local conditions favored for heavy rainfall occurrence over southwestern China and southeastern China were different, including the underlying surface conditions, the impact of weather systems and cold air activity (Yuan et al, 2018;Li and Li, 2019;Yuan et al, 2019;Chen and Li, 2022;Li et al, 2022), etc. These findings suggested that the characteristics of rainfall and its mechanisms may have regional differences in southern China.…”
Section: Discussionmentioning
confidence: 99%
“…The two-dimensional horizontal frontogenesis function was calculated to investigate the frontogenesis related to rainfall process (Ninomiya, 1984), which was also used in Yuan et al (2019) and shown good performance in diagnosing frontogenesis over southern China. Empirical orthogonal function (EOF) analysis was used to investigate the modes of SBT variation.…”
Section: Identification Of the Sbtmentioning
confidence: 99%
See 3 more Smart Citations